Keeping the War Outside the Frame: Ellipsis as a Means of Redirection Toward Women's Perspectives in Two War Narratives - Cubillos, Bernardita M. (The Nordic Journal of Aesthetics, 2023)
This article explores how cinema’s material discontinuity can stimulate the attention of a distracted audience and prompt reflection on historical violence. By examining Yasujiro Ozu’s Sanma no aji (1962) and Greta Gerwig’s Little Women (2019), it argues that ellipsis is a powerful technique used to construct an argument about the relationship between war and women’s social roles. Specifically, the article analyses how these films use the ellipsis to enhance the resistance of women who act against the official thread of History. Finally, the findings highlight the potential of cinema to challenge dominant narratives and encourage alternative approaches to representing violence and social roles.